2009
DOI: 10.1063/1.3224886
|View full text |Cite
|
Sign up to set email alerts
|

Improved precision in strain measurement using nanobeam electron diffraction

Abstract: Improvements in transmission electron microscopy have transformed nanobeam electron diffraction into a simple and powerful technique to measure strain. A Si0.69Ge0.31 layer, grown onto a Si substrate has been used to evaluate the precision and accuracy of the technique. Diffraction patterns have been acquired along a ⟨110⟩ zone axis using a FEI-Titan microscope and have been analyzed using dedicated software. A strain precision of 6×10−4 using a probe size of 2.7 nm with a convergence angle of 0.5 mrad has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 14 publications
(15 reference statements)
1
102
1
Order By: Relevance
“…Strain measurement via diffracted peak location is a well understood result of Bragg's law, and has been successfully performed using several different experimental techniques [16,10,11]. For NBED, the first and most important step is proper data acquisition.…”
Section: Measuring Lattice Vectors From Nanobeam Electron Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain measurement via diffracted peak location is a well understood result of Bragg's law, and has been successfully performed using several different experimental techniques [16,10,11]. For NBED, the first and most important step is proper data acquisition.…”
Section: Measuring Lattice Vectors From Nanobeam Electron Diffractionmentioning
confidence: 99%
“…With NBED this is not a problem and FOV is usually limited by the storage space of the data acquisition system or the sample stability. With the introduction of high speed direct electron detectors, a large number of diffraction patterns can be obtained from a single sample, covering a very large field of view without concerns for sample drift or other instabilities [10,2,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 The sensitivity and resolution of the Nano Beam Diffraction (NBD) method is comparable to other methods, and the sample preparation procedure is relatively simple. [8][9][10] Recent studies using the NBD method have reported strain evolution in epitaxial Ge layers in narrow oxide trenches, 11,12 and strain distribution in fin-FET structures was reported using a combination of NBD and the finite element method (FEM). 13 In the present study, we report the crystallinity and strain distribution of epitaxial Si 1-x Ge x selectively grown by UHV-CVD.…”
Section: Introductionmentioning
confidence: 99%
“…The electron beam is scanned across the region of interest in STEM mode and the patterns are automatically processed using an in-house software to provide strain profiles. This technique is extremely easy to perform and 1D strain profiles with a sensitivity of 0.06 % has now been demonstrated with a spatial resolution of 3 nm [5]. The main problem with NBED is that the probe is not perfectly parallel, thus the diffraction pattern is composed of discs containing dynamical effects leading to incorrect measurements of the strain.…”
Section: Introductionmentioning
confidence: 99%